An orderly charging and discharging strategy for electric vehicles based on cooperative game and dynamic time-of-use pricing - Zhengyu SHU; Wencan LIU; Huangqiang LI; Can WANG; Qin YAO (电力工程技术)
Currently, the distribution grid is substantially pressured due to the charging requirements of electric vehicles during peak hours with the rapid growth of electric vehicles. Existing studies indicate that the power supply pressure on the distribution grid can be effectively mitigated by the orderly charging and discharging scheduling of electric vehicles. However, the disparities in charging and discharging needs among different electric vehicle users are not considered by the majority of electric vehicle charging station operators, which treat the charging and discharging scheduling of electric vehicles uniformly, thus increasing grid pressure. To address this, an optimization approach for electric vehicle charging scheduling based on electricity price guidance is proposed in this paper, for the game between electric vehicle operators and users under a cooperative game framework. Additionally, a dynamic time-of-use optimized charging and discharging simulation model for electric vehicles is constructed. In the solution process, an improved fruit fly optimization algorithm (FOA) is uesd to plan the charging periods of electric vehicles. Eventually, the feasibility and economic advantages of the proposed strategy are verified through case study simulation analysis. Compared to the existing fixed electricity price strategy, the proposed strategy not only effectively reduces the peak-to-valley differences of the grid load and prevents new load peaks but also improves the benefits for both electric vehicle operators and users.